2020
DOI: 10.2196/preprints.25916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging Virtual Reality and Augmented Reality to Combat Chronic Pain in Youth: Position Paper From the Interdisciplinary Network on Virtual and Augmented Technologies for Pain Management (Preprint)

Abstract: UNSTRUCTURED Background: Virtual reality (VR) and augmented reality (AR) interventions are emerging as promising tools in the treatment of pediatric chronic pain conditions, but in this young field there is little consensus to guide the process of engaging in the development and evaluation of targeted VR-based interventions. Methods: The INOVATE-Pain consortium aims to advance the field of VR for pediatric chronic pain rehabilitation by providing guidance for best practices in the desig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Moving on from critiques of VR headsets, peripherals, and related technologies, Bookman then moved onto to Step 3, inviting students to consider how software mechanics could similarly create barriers. Citing scholarship by inclusion consultants who specialize in VR such as Thomas Logan, Bookman suggested that many VR applications demanded a high degree of technical literacy and frequently lacked accessibility features like captions, audio descriptions, and color contrast options (Logan, 2021). Furthermore, developers often presumed that users had great capacities for learning, memorization, and reproduction of inputs when designing apps for work, play, and other activities.…”
Section: Investigate Vr Software Accessibility (Step 3)mentioning
confidence: 99%
“…Moving on from critiques of VR headsets, peripherals, and related technologies, Bookman then moved onto to Step 3, inviting students to consider how software mechanics could similarly create barriers. Citing scholarship by inclusion consultants who specialize in VR such as Thomas Logan, Bookman suggested that many VR applications demanded a high degree of technical literacy and frequently lacked accessibility features like captions, audio descriptions, and color contrast options (Logan, 2021). Furthermore, developers often presumed that users had great capacities for learning, memorization, and reproduction of inputs when designing apps for work, play, and other activities.…”
Section: Investigate Vr Software Accessibility (Step 3)mentioning
confidence: 99%